Expression of IL‐7Rα and KLRG1 defines functionally distinct CD8+ T‐cell populations in humans. Issue 5 (25th March 2019) - Remmerswaal, Ester B. M.; Hombrink, Pleun; Nota, Benjamin; Pircher, Hanspeter; ten Berge, Ineke J. M.; van Lier, René A. W.; van Aalderen, Michiel C.
Abstract: During acute viral infections in mice, IL‐7Rα and KLRG1 together are used to distinguish the short‐lived effector cells (SLEC; IL‐7Rα lo KLRG hi ) from the precursors of persisting memory cells (MPEC; IL‐7Rα hi KLRG1 lo ). We here show that these markers can be used to define distinct subsets in the circulation and lymph nodes during the acute phase and in "steady state" in humans. In contrast to the T cells in the circulation, T cells derived from lymph nodes hardly contain any KLRG1‐expressing cells. The four populations defined by IL‐7Rα and KLRG1 differ markedly in transcription factor, granzyme and chemokine receptor expression. When studying renal transplant recipients experiencing a primary hCMV and EBV infection, we also found that after viral control, during latency, Ki‐67‐negative SLEC can be found in the peripheral blood in considerable numbers. Thus, combined analyses of IL‐7Rα and KLRG1 expression on human herpes virus‐specific CD8 + T cells can be used to separate functionally distinct subsets in humans. As a noncycling IL‐7Rα lo KLRG1 hi population is abundant in healthy humans, we conclude that this combination of markers not only defines short‐lived effector cells during the acute response but also stable effector cells that are formed and remain present during latent herpes infections. Abstract : Functional CD8+ T‐cell populations among acute phase effector cells and memory cells can be distinguished by differences in the expression of IL‐7Rα and KLRG1. Cells with a IL‐7Rαlo/KLRG1hi phenotype, previously defined as short‐lived effector cells in mice, persist long after the acute phase of primary CMV infection in humans.